2022
DOI: 10.3390/molecules27061752
|View full text |Cite
|
Sign up to set email alerts
|

Laser Light Treatment Improves the Mineral Composition, Essential Oil Production and Antimicrobial Activity of Mycorrhizal Treated Pelargoniumgraveolens

Abstract: Pelargonium graveolens, rose-scented geranium, is commonly used in the perfume industry. P. graveolens is enriched with essential oils, phenolics, flavonoids, which account for its tremendous biological activities. Laser light treatment and arbuscular mycorrhizal fungi (AMF) inoculation can further enhance the phytochemical content in a significant manner. In this study, we aimed to explore the synergistic impact of these two factors on P. graveolens. For this, we used four groups of surface-sterilized seeds: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Using the disc diffusion method, the studied sprouts’ antibacterial activity was assessed [ 15 ]. Using a vernier caliper to measure the inhibition zone, the antibacterial activity was ascertained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the disc diffusion method, the studied sprouts’ antibacterial activity was assessed [ 15 ]. Using a vernier caliper to measure the inhibition zone, the antibacterial activity was ascertained.…”
Section: Methodsmentioning
confidence: 99%
“…The pre-soaking of seeds and the application of elicitation with plant hormones are sustainable methods used to enhance bioactive compound accumulation in broccoli and radish sprouts, thus improving their antioxidant activities [ 14 ]. Similarly, the probable synergistic effects of laser light application on treated Pelargonium graveolens and mycorrhizal enhanced mineral and essential oil content as well as antibacterial activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other laser treatments on fungi such as an arbuscular mycorrhizal fungi (AMF) inoculum have been used. Okla et al (2022) found that the application of laser light together with a mycorrhizal inoculation on Pelargonium graveolens significantly improved plant biomass and nutrient content. The treated samples also showed an increase in the amount of essential oils and secondary metabolites as compared to the untreated samples.…”
Section: Interaction Between Plants/micro-organisms and Laser Technologymentioning
confidence: 95%
“…Laser beams can be useful not only in the control of fungi directly in isolation or naturally in the case of agricultural seeds, water, soil, food, etc., but they can also be used to modify the active elements of the fungus itself (Geweely et al, 2011) and those of plants with fungal properties (Aladjadjiyan, 2007;Ali et al, 2022;Al-abedi et al 2023) or indeed those of bactericides (Balkhyour et al, 2021;El-Adly et al, 2007;Zrig et al 2022;Okla et al 2022), it has been reported that laser light could be used to enhance their properties. However, when they are used for this purpose, it is still of interest to define the appropriate radiation parameters and also the optical and thermal characteristics of the biological element in question.…”
Section: Laser Beams As Enhancers Of Active Elementsmentioning
confidence: 99%
“…Scientists have identified the chemical compounds and antidiabetic properties of P. graveolens essential oil and have detected 36 chemical components present in it 15 . On the other hand, Džamić et al reported 56 chemicals; antifungal and antioxidant activity of P. graveolens essential oil 16 .Other researchers discovered 15 extra chemicals in P. graveolens essential oil and they measured the antioxidants activity by DPPH assay 17,18 .Okla et al studied the effect of laser on mineral content of P. graveolens and they found 7 minerals including zinc and iron 17 . Boukhris et al investigated the chemical compounds and biological functions of polar extracts and essential oil and showed that β-citronellol as the primary constituent of the oil part and nine flavonoids were identified as well 19 .…”
Section: Introductionmentioning
confidence: 99%